The Influence of Destination Branding and the TikTok Platform on Purchase Decisions at DEWI Pandawa, Ponokawan Village, Krian, Sidoarjo - Zulkarnain, Bunga; Augustinah, Fedianty; Listyawati, Liling (International Journal of Scientific Research and Management (IJSRM), 2024)
This research analyzes the impact of destination branding and the use of TikTok on tourists' purchasing decisions at the tourist destination (Dewi Pandawa) Ponokawan, Krian, Sidoarjo. With a quantitative approach, data was collected from 100 respondents aged 15-40 who are active on TikTok. The results show that effective branding strengthens the emotional connection and purchasing decisions of tourists. TikTok plays a role in attracting a wider audience with engaging content, increasing awareness and interest in destinations. Analysis with SPSS ensures there is no multicollinearity and heteroscedasticity, confirming the validity of the regression model. Branding and TikTok have proven to be important factors in influencing consumer behavior in the tourism sector, providing insights to enhance marketing through quality content and consistent branding. This research also identifies the need for quality content and the risk of dependency on a single social media platform.